Characterisation of the Function of a SINE-VNTR-Alu Retrotransposon to Modulate Isoform Expression at the MAPT Locus - Fröhlich, Alexander; Pfaff, Abigail L.; Bubb, Vivien J.; Koks, Sulev; Quinn, John P. (Frontiers in Molecular Neuroscience, 2022)
SINE-VNTR-Alu retrotransposons represent one class of transposable elements which contribute to the regulation and evolution of the primate genome and have the potential to be involved in genetic instability and disease progression. However, these polymorphic elements have not been extensively analysed when addressing the missing heritability of neurodegenerative diseases, including Parkinson’s disease (PD) and amyotrophic lateral sclerosis (ALS). SVA_67, a retrotransposon insertion polymorphism, is located in a 1.8 Mb region of high linkage disequilibrium, called the MAPT locus, which is known to contribute to increased risk of developing PD, frontotemporal dementia and other tauopathies. To investigate the role of SVA_67 in directing differential gene expression at this locus, we characterised the impact of SVA_67 allele dosage on isoform expression of several genes in the MAPT locus using the datasets from both the Parkinson’s Progression Markers Initiative and New York Genome Center Consortium Target ALS cohort. The Parkinson’s data was from gene expression in the blood and the ALS data from a variety of CNS regions and allowed us to demonstrate that SVA_67 presence or absence correlated with both isoform- and tissue-specific expression of multiple genes at this locus. This study highlights the importance of addressing SVA polymorphism in disease genetics to gain insight into a better understanding of the role of these regulatory domains to a variety of neurodegenerative diseases.